Examining the influence of three-dimensional paternalistic leadership on turnover intention among milllenial employees in China - Zong Lu Song; Tze Cheng Chew; Borhan Abdullah (Global Academic Excellent, 2024)
This study explores the intricate relationship between three-dimensional paternalistic leadership and the turnover intentions of millennial employees within the context of China. Using a sample of 241 millennial employees from private enterprises in China, the research employs SPSS and PLS analysis to uncover significant findings. The results reveal that three-dimensional paternalistic leadership directly impacts the turnover intentions of millennial employees. However, the study has limitations due to the use of single respondent and cross-sectional data, which may affect the rigor and generalizability of the findings. Despite these limitations, the study offers important management and decision-making insights, enriching the understanding of three-dimensional paternalistic leadership and its effects on millennial employees' turnover intentions, thus encouraging further research in this area.